Thoracoscopic Trans-mitral Septal Myectomy for Hypertrophic Obstructive Cardiomyopathy in the Elderly - Wei, Peijian; Liu, Jian; Ma, Jiexu; Liu, Yanjun; Tan, Tong; Wu, Hongxiang; Zhu, Wei; Chen, Zhao; Chen, Jimei; Zhuang, Jian; Guo, Huiming (Frontiers in Cardiovascular Medicine, 2022)
Background: The thoracoscopic trans-mitral approach can not only facilitate exposure of the ventricular septum, mitral valve, and subvalvular apparatus, it also enables the surgeons to perform concomitant mitral valve intervention. This study aimed to determine the safety and efficacy of thoracoscopic trans-mitral septal myectomy in elderly patients with hypertrophic obstructive cardiomyopathy (HOCM). Methods: We reviewed the demographic and clinical characteristics and outcomes of patients who underwent thoracoscopic trans-mitral septal myectomy in our center between April 2019 and April 2021. The population was divided into a younger group (<60 years) and an elderly group (≥60 years). Results: There were 46 and 20 patients in the young and elderly groups, respectively. The majority of patients in the elderly group were female (39.1% vs 80.0%, P<0.01). Patients in the elderly group were more likely to be in New York Heart Association Class IV (2.2% vs 80.0%, P<0.01). The European System for Cardiac Operation Risk Evaluation II predicted mortality rate were significantly higher (3.97±1.81% vs 1.62±0.86%, P<0.01) in the elderly group. In the elderly group, a patient converted to median sternotomy due to left ventricular posterior free wall rupture following septal myectomy and mitral bioprosthetic valve replacement. The patient then underwent double-patch sandwich repair for rupture and mitral mechanical valve replacement and was eventually discharged. All patients in the elderly group were discharged, while one in the younger group died. No patient in the elderly group required permanent pacemaker implantation versus one in the younger group. Patients in the elderly group were more likely to spend more time in the ICU than those in the younger group. However, there was no significant intergroup difference in in-hospital mortality or complications. Importantly, the left ventricular outflow tract pressure gradient was significantly decreased from 96.15±32.89 mmHg to 8.2±3.42 mmHg with no residual obstruction in the elderly group. The interventricular septal thickness was significantly decreased from 19.73±3.14 mm to 11.30±2.23 mm. Postoperative mitral regurgitation severity was significantly improved in the elderly group. Conclusion: This study demonstrated that thoracoscopic trans-mitral septal myectomy is a feasible option for selected elderly patients with satisfactory outcomes similar to those of young patients.